Bauhinia guianensis Aubl., a Plant from Amazon Biome with Promising Biologically Active Properties: A Systematic Review - Koga, Rosemary de Carvalho Rocha; Santos, Abrahão Victor Tavares de Lima Teixeira dos; Sarquis, Rosângela do Socorro Ferreira Rodrigues; Carvalho, José Carlos Tavares (Pharmacognosy Reviews)
Introduction: The literature demonstrates a scarcity of pharmacological and toxicological studies that reveal the usefulness and safety in using products that present as active raw material Bauhinia guianensis Aubl. This study aimed to research the botanical aspects, traditional use, and phytochemical composition of the vegetal species Bauhinia guianensis Aubl., described in international scientific literature. Methods: A search was carried out in different databases, specifically in the Biblioteca Virtual em Saúde-BVS, Embase, Lilacs, PubMed/Medline, CAPES Periodic, ResearchGate, SciELO, ScienceDirect and Scopus, with the descriptor “Bauhinia guianensis Aubl.”, published between 1996 and 2020. Results: The results show few studies on this vegetal species, mainly related to the in vivo study of the anti- inflammatory and antinociceptive activities that extracts from both the plant how much of your endophytic fungi can present. Conclusion: It is also important to identify the active constituents since there are rare analyses of the composition and structure of metabolites present in this plant or its endophytic fungi. This plant species is a promising source for obtaining biologically natural compounds that validate the ethanopharmacological use of Bauhinia guianensis Aubl.
Keywords: Bauhinia guianensis Aubl.; Botanical aspects; Phytochemical composition; Ethnopharmacology; Ethnobotany; Amazonia.